Impact of the COVID-19 lockdown on routine vaccination in Pakistan: a hospital-based study. Issue 12 (2nd December 2021) - Rahman, Saeed Ur; Haq, Faiz Ul; Imran, Muhammad; Shah, Asaf; Bibi, Naeema; Khurshid, Robina; Romman, Muhammad; Gaffar, Fatema; Khan, Muhammad Iqbal
ABSTRACT: The effect of the coronavirus disease (COVID-19) pandemic on routine vaccination in low- and middle-income countries are scarce. The current pandemic has disrupted routine immunization globally. We aimed to analyze the effect of COVID-19 pandemic on routine immunizations practice in Pakistan. A retrospective study was conducted. The data were extracted from the immunization registry in order to assess the disruption in routine immunization coverage during 5 months of the lockdown period. We compared 5 months post lockdown against the baseline period of 5 months preceding lockdown. To broaden the horizon of our research we also collected data of vaccination from rural areas within the country. The results of the current study showed that on average, there was a disruption in routine immunization by 36% during lockdown when compared with the prepandemic period. The largest decline was observed for measles vaccination with a decline of 48%. In rural areas there was a lower decline in vaccination coverage with the highest decline noted for rotavirus vaccination of 15%. This monthly decrease in routine vaccination continued to be at a decline for several months during lockdown; however, it slightly increased post lockdown. In conclusion, on average, there was more than 30% declined in routine vaccination during the lockdown period, while somewhat improved post lockdown, i.e. 12%. Thus, this ongoing pandemic is a reminder for the national immunization programs to consider to tackle the disruption in routine immunization, otherwise, this continued disruption may lead to secondary outbreaks of vaccine preventable diseases amongst the public.